(untitled) (Cambridge, 2002)
This book exposes readers to a wide variety of new and promising perspectives for enhancing the scope of judgment and decision-making research. They bridge the gap between traditional paradigms and new lines of inquiry; expand awareness of new theories and approaches; and demonstrate how alternative approaches can enhance understanding.
Keywords: Decision making,Judgment,Ra quyết định,Sự đánh giá